Long-Term Complications of Anterior Chamber Iris Claw Lens - Siddhi Goel; Anin Sethi; Pranita Sahay; Prafulla K. Maharana; Jeewan S. Titiyal (Delhi Journal of Ophthalmology)
Cases of aphakia with no capsular support can be managed with anterior chamber intraocular lens (ACIOL), iris fixated IOL or scleral fixated IOL(SFIOL). The procedure of choice depends on the status of the patient’s eye as well as the surgeon's experience. Iris-claw lens implantation is an effective method for correction of aphakia with several advantages such as having fewer complications, with its easy placement and good visual outcomes. Herein, we report a case of a 42-year-old male patient who presented with pseudophakic bullous keratopathy with secondary glaucoma as a complication of anterior chamber iris-claw lens.